Physiological and biochemical changes in seeds of karanj (Pongamia pinnata) under different storage conditions - KUMAR, SANTOSH; RADHAMANI, J; SRINIVASAN, KALYANI (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted to elucidate the possible physiological and biochemical changes associated with seed deterioration during storage of karanj (Pongamia pinnata L.) seed. The seeds of variety ‘Bak 49’ (‘IC430529’) were extracted, processed and stored at three different levels of relative humidity (RH) (75%, 33% and 5.5%) and temperatures (4°C, 20°C and ambient). The seed viability pattern, physiological and biochemical parameters under different conditions were monitored at regular intervals to assess the effect of storage. Among the different RH treatments, 33% RH showed significantly higher values for viability and vigour over 5.5% and 75% RH at all temperatures. The biochemical parameters like electrical conductivity of seed leachates and lipid peroxidation under different treatments showed significantly increased values with seed deterioration. The level of total soluble sugars increased gradually, whereas total soluble proteins and enzyme activity (dehydrogenase and acid phosphatase) decreased with storage period in all the treatments. The optimal conditions for extending seed storability in karanj without having any adverse effect on physiological and biochemical parameters were 4°C and 20°C and 33% RH. This study could possibly be helpful for conventional storage of pongamia seeds on large scale and can be further exploited in other orthodox tree species.